LABEL HALAL PADA PRODUK PANGAN KEMASAN DALAM PERSPEKTIF PERLINDUNGAN KONSUMEN MUSLIM - Muslimah, Siti (Yustisia, 2012)
AbstractThe purpose of the research is to know how to give halal label on the packaging food product to protect muslim consumer and to know the obstacles in giving halal label on the packaging food product to protect muslim consumer. The research is yuridis empiris and the method used is descriptive avaluative. The research data are premier data and secondary data (premiere law matter, secondary law matter, and tertiary law matter). Technique of collecting the data are interview and documentary. The analysis of data is qualitative by using theoritical interpretation technique. The results of the research concluded that halal label on packaged food product is not yet provide maximum protection against consumer rights. There are still a halal labeling by manufacturers of food packaging without proposing halal certificate and without the checking procedure from the Assessment Agency of Food and Drugs of Indonesian Islamic Council (LPPOM MUI). The obstacles in the halal labeling of food products packaged in providing protection of moslems consumer rights are the legal foundation about halal labelling for food still weak, the presumption the certification process is expensive as well as the long time procedure, complicated and convoluted, the lack of legal awareness of food manufacturers packaging and is less critical and weak bargaining position of moslem consumers.Keywords: halal label, protection, muslim consumer.